Etiology, clinical profile, and immediate outcome of neonatal encephalopathy in Northeast India: A hospital-based cross-sectional study - Anamika Kumari; Sudip Dutta; Ashish Pradhan; Sudesh Kumar; Maitreyi Ojha (Asian Journal of Medical Sciences, 2022)
Background: Neonatal encephalopathy (NE) is one of the important causes contributing to neonatal death and disability. Knowledge about associated probable risk factors of NE will be helpful in developing strategies for proper intervention and early management.